Gender discourse and Malawian rural communities: a study of the meaning the people of traditional authority Likoswe of Chiradzulo make from human rights and gender messages - Manda, Levi Zeleza (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2002)
Contrary to earlier beliefs and media theories such as the hypodermic needle or magic bullet, the audience of public communication is not a passive homogenous mass that easily succumbs to media influence. The audience is active, that is, it makes an effort to interpret media content. Depending on predisposing cultural, political, religious, or economic factors the audience makes different meanings from media texts. Media messages are not wholly controlled by producers, although the producers have their preferred and expected readings. Using qualitative research techniques associated with ethnographic and cultural studies (notably focus group discussions), this study sought to explore the meanings rural people in Malawi make out of human rights and gender messages broadcast on radio and through music. Interpreted against Stuart Hall's (1974b) Encoding and Decoding model, the study concludes that while rural communities understand and appreciate the new sociopolitical discourse, they take a negotiated stance because they have their own doubts and fears. They fear losing their cultural identity. Additionally, men, in particular, negotiate the messages because they fear losing their social power over land, property and family.
Keywords: Human rights -- Malawi; Mass media in community development -- Malawi; Communication in community development -- Malawi; Mass media -- Social aspects -- Malawi; Mass media criticism -- Malawi; Women's rights -- Malawi; Sex role -- Malawi